The Effect of School Administrators’ Spiritual Leadership Style on School Culture - Mustafa Özgenel; Samet Ankaralıoğlu (Spiritual Psychology and Counseling, 2020)
This study aims to determine whether administrators’ spiritual leadership style predicts school culture according to the perceptions of teachers working at different school levels. The study was carried out according to the correlation survey model used in quantitative research methods. The population of the study consists of 3657 teachers working in primary, secondary, and high schools in the Kartal district of Istanbul in the 2018-2019 academic year. The sample of the study was selected using a simple random sampling method; It consists of a total of 446 teachers working in primary, middle school, and high school levels. The Managerial Spiritual Leadership Perception Scale that was developed by Akıncı and Ekşi (2017) and The School Culture Scale that was developed by Terzi (2005) were used to collect the data. Data were analyzed by t-test, ANOVA, correlation, and regression analysis. The findings of the study showed that there was a moderate and positive relationship between school culture and the spiritual leadership styles of administrators according to teachers’ perceptions. In addition, it was concluded that the spiritual leadership styles of school administrators were a predictor of school culture according to the teachers’ perceptions. While significant differences were found between gender and school- level variables in the support culture sub-dimension of the school culture, age and school-level variables in the success culture sub-dimension, age, occupational seniority, and school-level variables in the bureaucratic culture sub-dimension, age and school-level variables in the task culture sub-dimension, there was no difference between the sub-dimension of school culture and educational status. While there was a significant difference in the level of spiritual leadership perceived by teachers according to the school level variable, there was no significant difference according to the variables of gender, educational level, age, and professional seniority. According to the results of the research, some suggestions were developed.